1980
DOI: 10.1351/pac198052010055
|View full text |Cite
|
Sign up to set email alerts
|

Glycopeptides of human teratoma stem cells

Abstract: -Glycopeptides of human teratoma cells were studied. Two glycopeptide fractions (Fractions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The presence of monosaccharide constituents like mannose, galactose, sialic acid [lo] and fucose [7,10] in the PA 1 cell glycopeptides of large size suggested that additional components resembling the keratan sulfates [32] may accompany the glycosaminoglycuronans. In order to see whether keratansulfate-like molecules are really present we treated the fraction of the large-sized saccharides and glycopeptides with endo-j-galactosidase from Escherichia ,freundii and analyzed the digests by gel filtration.…”
Section: Action Of Endo-p-galactosidase On the Fraction Of The Large-mentioning
confidence: 99%
“…The presence of monosaccharide constituents like mannose, galactose, sialic acid [lo] and fucose [7,10] in the PA 1 cell glycopeptides of large size suggested that additional components resembling the keratan sulfates [32] may accompany the glycosaminoglycuronans. In order to see whether keratansulfate-like molecules are really present we treated the fraction of the large-sized saccharides and glycopeptides with endo-j-galactosidase from Escherichia ,freundii and analyzed the digests by gel filtration.…”
Section: Action Of Endo-p-galactosidase On the Fraction Of The Large-mentioning
confidence: 99%